pls answer.

Asked by  | 4th May, 2009, 08:33: AM

Expert Answer:

Let x = 1/2 + 1/3 + .......... + 1/2008,

and y = 1/2 + 1/3 + .......+ 1/2007,

then the given expression is written as,

(x)(1+y) - (1+x)(y)

= x + xy - y - xy

= x - y

= (1/2 + 1/3 + .......... + 1/2008) - (1/2 + 1/3 + .......+ 1/2007)

= 1/2008

So the given expression simplifies to 1/2008.

Regards,

Team,

TopperLearning.

Answered by  | 29th Aug, 2009, 11:00: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.